Empowering Language Learners: Innovative Strategies for 21st Century English Education - Siti Meutia Sari (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The rapid evolution of the 21st century has brought significant shifts in the way English language education is approached and delivered. This study explores innovative strategies aimed at empowering language learners to meet contemporary communicative demands and to develop essential 21st-century skills. Utilizing a qualitative descriptive method, the research examines five major strategies: technology integration, project-based learning, storytelling and creative expression, learner autonomy, and gamification. Findings reveal that these strategies not only enhance linguistic proficiency but also promote higher-order thinking skills, learner engagement, creativity, collaboration, and digital literacy. Furthermore, the study highlights the evolving role of educators as facilitators and mentors in creating dynamic, inclusive learning environments. The implementation of these approaches is found to significantly contribute to more effective, relevant, and empowering English language education. This paper concludes that a transformative shift in pedagogical practices is necessary to prepare learners for meaningful participation in an increasingly globalized world.